2011
DOI: 10.3758/s13423-011-0085-x
|View full text |Cite
|
Sign up to set email alerts
|

Testing protects against proactive interference in face–name learning

Abstract: Learning face-name pairings at a social function becomes increasingly more difficult the more individuals one meets. This phenomenon is attributable to proactive interference-the negative influence of prior learning on subsequent learning. Recent evidence suggests that taking a memory test can alleviate proactive interference in verbal list learning paradigms. We apply this technique to facename pair learning. Participants studied four lists of 12 face-name pairings and either attempted to name the 12 faces ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(113 citation statements)
references
References 17 publications
7
105
0
1
Order By: Relevance
“…These data were analysed by a mixed analysis of variance (ANOVA) with Interim test as a between-subjects variable and List (1-5) as a within-subjects variable. A within-subjects contrast showed that there was a negative linear regression of study time across lists, F (1,28) These results imply that participants in the Interim Test group were better able to control their retrieval from the current list and that the memory search set in the Interim Test group was smaller than that in the No Interim Test group (Weinstein et al, 2011).…”
Section: Encoding Timementioning
confidence: 83%
See 4 more Smart Citations
“…These data were analysed by a mixed analysis of variance (ANOVA) with Interim test as a between-subjects variable and List (1-5) as a within-subjects variable. A within-subjects contrast showed that there was a negative linear regression of study time across lists, F (1,28) These results imply that participants in the Interim Test group were better able to control their retrieval from the current list and that the memory search set in the Interim Test group was smaller than that in the No Interim Test group (Weinstein et al, 2011).…”
Section: Encoding Timementioning
confidence: 83%
“…There was no significant difference in study time between the groups on any of Lists 1-4, 0.7 ≤ ts ≤ 1.85, .95 ≥ ps ≥ 0.08. These results imply that participants in the Interim Test group were better able to control their retrieval from the current list and that the memory search set in the Interim Test group was smaller than that in the No Interim Test group (Weinstein et al, 2011). …”
mentioning
confidence: 82%
See 3 more Smart Citations